Effects of dead-band and set-point settings of on/off controllers on the energy consumption and equipment switching frequency of a residential HVAC system. (November 2016) - Afram, Abdul; Janabi-Sharifi, Farrokh
Highlights: A combined grey-box model of the residential HVAC system is developed and calibrated. Energy consumption analysis of active HVAC subsystems is carried out. Effects of on/off controller set-point and dead-band are investigated. HVAC energy consumption and equipment switching frequency is optimized. Optimum settings for set-points and dead-bands of on/off controllers are found. Abstract: Residential heating, ventilation and air conditioning (HVAC) systems generally employ simple on/off controllers to regulate the temperature of water and air in different subsystems. Selection of set-point of a controlled process and dead-band of controller affects the process regulation, energy consumption and actuator switching frequency. This article presents a calibrated model of a residential HVAC system. Temperature of two zones and buffer tank (BT) is regulated using on/off controllers. Non optimum controller settings result in poor regulation, higher energy consumption and higher equipment wear. The purpose of this article is to find optimum set-point and dead-band settings for on/off controllers in order to improve temperature regulation, reduce energy consumption and decrease equipment wear by reducing the switching frequency of HVAC equipment without scarifying thermal comfort of occupants.